Indonesia’s IKN Nusantara Project: Political Legitimacy, State Capacity, and Capital Relocation in Comparative Perspective - Vania Citra Permatasari (Indonesian Political Transformation, 2025)
Indonesia's decision to relocate its national capital from Jakarta to Nusantara represents one of the most ambitious state-building projects undertaken in the twenty-first century. Beyond its developmental objectives, the project raises important questions regarding political legitimacy, governance capacity, institutional continuity, and national identity. Existing literature has primarily examined the economic and urban planning dimensions of capital relocation, leaving its political implications underexplored. This article investigates how the Nusantara project reflects Indonesia's broader political transformation by analyzing the relationship between state capacity, political legitimacy, and administrative reform. Using a comparative qualitative approach, the study examines Indonesia alongside previous capital relocation experiences in Brazil, Kazakhstan, Nigeria, and Malaysia. Data are collected through policy document analysis, elite interviews, and comparative institutional analysis. The study argues that successful capital relocation depends not only on infrastructure development but also on sustained political legitimacy, bureaucratic effectiveness, stakeholder participation, and long-term institutional commitment. Preliminary findings suggest that while Nusantara provides opportunities to modernize governance and reduce regional inequality, significant challenges remain concerning democratic accountability, environmental governance, fiscal sustainability, and policy continuity across political administrations. The article develops a comparative analytical framework explaining how capital relocation functions as a political transformation strategy rather than merely an urban development initiative. By integrating comparative politics with public administration, this study contributes to broader discussions on state-building, governance innovation, and institutional resilience in emerging democracies. The findings also provide practical lessons for countries considering large-scale administrative relocation as part of national transformation agendas.